Enhancing Islamic Higher Education Image as the Halal Industry Driving Indonesian Halal Industries - Riofita, Hendra; Iqbal, Muhammad Amjed (Journal of Digital Marketing and Halal Industry, 2022)
Islamic higher education image as the halal industry driving Indonesian halal industries should be improved along with the increasing role of higher educations to succeed halal industry, through the services provided to the implementation of three pillars in the fields of academics, research and supporting elements or community services. This study aims to develop e-halal service quality, as an electronic service to enhance the image. Considering that electronic services are part of service innovation, and there is not enough evidence for such service innovation to enhance image, this study also aims to develop service recovery as an antecedent of e-halal service quality and Islamic higher education image, respectively. Furthermore, considering the image as the halal industry driving Indonesian halal industries is a consequence of service recovery and e-halal service quality, respectively, this study also develops the variables based on social exchange theory. Primary data is taken using a questionnaire sent to the leadership elements of Indonesian Private Islamic Higher Education via google link, and analyzed using SPSS and Amos programs. The findings demonstrate that e-halal service quality and service recovery, respectively have significant effect on Islamic higher education image as the halal industry driving Indonesian halal industries. Service recovery also has a significant effect on e-halal service quality and can be a trigger for e-halal service quality to enhance   Islamic higher education image as the halal industry driving Indonesian halal industries. Therefore, service recovery and e-service quality can develop social exchange theory to enhance Islamic higher education image as the halal industry driving Indonesian halal industries.